PENGARUH DIFERENSIASI PRODUK, KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN PADA KUE TRADISIONAL SERABI PAK RAJA DI NEGERI LAMA - Nuri Zulfa Elina; Elida Florentina Sinaga Simanjorang; Fadzil Hanafi Asnora (JOEL: Journal of Educational and Language Research, 2022)
In the culinary industry, consumer loyalty can be achieved if the company is able to provide products, especially in the form of different foods or have product differentiation and also quality products and have a familiar brand image to consumers. The purpose of this study is to determine the influence of product differentiation, product quality and brand image on consumer loyalty. This research was conducted at Kedai Serabi Pak Raja Negeri Lama with a sample of 96 people with accidental sampling technique. Primary data collection was carried out using questionnaires and measurement scales using the Likert Scale with five answer choices. Based on the results of the analysis that has been carried out, it can be concluded that (1) product differentiation has a positive and significant effect on consumer loyalty and (2) the quality of the product has a positive and significant effect on consumer loyalty and (3) the brand image has a positive and significant effect on consumer loyalty to the Traditional Cake Serabi Pak Raja in the Old Country.